The Moderating Effect of Ownership Structure in Affecting CSR on Financial Performance - Vania Aqila Lituhayu (Syntax Literate, 2023)
CSR activities are becoming a trend that companies do to be able to compete in increasingly fierce business competition. The company's consistency in carrying out CSR activities can have an influence on the profits generated by the company, which is shown by the company's financial performance. However, there are factors that can influence CSR on financial performance, one of which is ownership structure. The company's managerial ownership structure will have an impact on how well business decisions are made. The ownership identity applied by the company will support management decision making in implementing CSR efforts and improving financial performance. This study was conducted to examine the effect of ownership structure as a moderating variable on the relationship between corporate social responsibility and financial performance in companies located in Indonesia and Singapore. Furthermore, it was also tested by comparing CSR disclosures in the two countries by focusing on companies listed on the LQ45 index and the Straits Times Index. The test analysis uses panel data regression analysis and Mann-Whitney test to determine the level of difference in CSR in Indonesia and Singapore. The results obtained are that there is no significant difference in CSR in Indonesian and Singaporean companies. Furthermore, the role of ownership structure in strengthening the relationship between CSR and financial performance can be proven in Singapore companies, but cannot be proven in Indonesian companies.